2019
DOI: 10.31334/bijak.v16i2.518
|View full text |Cite
|
Sign up to set email alerts
|

Model Financial Dan Teknologi (Fintech) Membantu Permasalahan Modal Wirausaha UMKM Di Indonesia

Abstract: The objectives of this study are (1) to find out the effect of technology-based financing models in helping entrepreneurial capital problems in society, Indonesia, (2) Knowing the types of technology-based financing models to help entrepreneurial capital problems in society, Indonesia, (3) Helping MSMEs capital in the future, (4) Helping solutions to business capital problems in entrepreneurial activities. Qualitative descriptive research is aimed at describing and describing existing phenomena, both natural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 5 publications
0
7
0
8
Order By: Relevance
“…Metode penelitian yang digunakan adalah studi literatur yang dibutuhkan dalam riset (Nazir, 2014) dari beberapa penelitian sebelumnya menyangkut dari kebijakan diatas (Ardiansyah, 2019;Barus, 2013;Danistyo, 2009;Muzdalifa, Rahma, dan Novalia, 2018;Nisa, 2016;Ratnasari, 2016;Rizal, Maulina dan Kostini, 2019;Sunarsi, 2020).…”
Section: Metodeunclassified
See 1 more Smart Citation
“…Metode penelitian yang digunakan adalah studi literatur yang dibutuhkan dalam riset (Nazir, 2014) dari beberapa penelitian sebelumnya menyangkut dari kebijakan diatas (Ardiansyah, 2019;Barus, 2013;Danistyo, 2009;Muzdalifa, Rahma, dan Novalia, 2018;Nisa, 2016;Ratnasari, 2016;Rizal, Maulina dan Kostini, 2019;Sunarsi, 2020).…”
Section: Metodeunclassified
“…Dari Gambar 4 Map Fintech diatas terhadap kebijakan UMKM terdapat 7 kebijakan dimana antara lain adalah: Kebijakan Fintech (KF), NPL Fintech (NPLF), Pelatihan Pelaku Usaha Fintech (PPUF), Pembiayaan Kredit Fintech (PKF), Penyaluran Kredit Fintech (PSKF), Tantangan Fintech (TF), Teknologi Fintech (TEF). Hasil ini didukung dari beberapa penelitian sebelumnya menyangkut dari kebijakan diatas (Ardiansyah, 2019;Barus, 2013;Danistyo, 2009;Muzdalifa, Rahma, dan Novalia, 2018;Nisa, 2016;Ratnasari, 2016;Rizal, Maulina dan Kostini, 2019;Sunarsi, 2020).…”
Section: Map Fintechunclassified
“…Currently, the number of MSMEs in Indonesia has increased significantly from year to year. According to the Central Bureau of Statistics in 2018, it was found that small and medium enterprises in Indonesia have increased every year besides that BPS also said the number of Micro, Small and Medium Enterprises (MSMEs) reached 64 million (Ardiansyah, 2019). This figure reaches 99.9 percent of all businesses operating in Indonesia, so it cannot be denied that Micro, Small and Medium Enterprises (MSMEs) located in all regions in Indonesia are one of the main drivers of the economy (Ardiansyah, 2019;Prianto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In which, these MSME actors have difficulties in obtaining business capital credit from banks. A long series of regulatory and administrative processes from banks has triggered difficulties for MSMEs to get credit for their business capital [8]. The more rapid development of this technology encourages the actors involved in the sector to continue making new innovations so that their products and works can continue to exist.…”
Section: Introductionmentioning
confidence: 99%